SMART MATERIALS IN SCULPTURAL EDUCATION - Sharma, Sorabh; B. Dhanalakshmi; Prasad S, Shankar; Malik, Mohit; Thakuriya, Kajal; Gupta, Mohit; Wawage, Pawan (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The introduction of intelligent materials in sculpture education is reshaping the ancient ways of providing art-making with dynamism in ability to react, deal, and sensitivity to the environment. In the present paper, the mechanisms of enhancing the expressive and functional possibilities of the sculpture at hand through the use of shape memory alloys and polymers, piezoelectric composites, and chromic substances are discussed. The paper examines their characteristics like actuation and self-modification, color-shift behavior, etc and the way these materials reconfigure the adaptive, kinetic and interactive artworks. This study extends to the field of education where interdisciplinary education is encouraged through the application of smart materials where material science, engineering, and digital fabrication are combined with artistic implementation. The study assesses the pedagogical value of integrating these new technologies through qualitative case studies, experimentation in the studio and examination of student initiated projects. Results indicate that smart materials promote innovation, creative problem-solving, and creativity as well as sustainable and responsive art practices. Nevertheless, there are still some difficulties, especially when it comes to material availability, price, technical restrictions, and the necessary expertise. In spite of these limitations, the study shows that purposeful curriculum development and practical exploration can be successful in facilitating the implementation of smart materials in the sculpture courses. Altogether, the present work emphasizes the importance of introducing smart materials into the art education process as the method of deepening the experiential learning practice and broadening the conceptual and practical boundaries of the sculptural practice.